PEMBUATAN GAME EDUKASI “HAFIZ QURAN” PADA PLATFORM ANDROID - Larasati, Kirey; Pragantha, Jeanny; Haris, Darius Andana (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
This game was made using Unity Game Engine with C# as a programming language and Photoshop for animation. This game consist of 5 mini games that are: Drag and Drop, Memory, Connect Verses, Guess Pictures and Puzzles. In the drag and drop game, the player must match the questions in the form of the existing Al-Quran writing with the existing picture. In the Memory, the player can only open the clue twice to choose the same picture. In the Connect Verse game, the player must connect the verse by selecting one of the multiple choices. In the Guessing Games, players must match an image with the corresponding name. In the Puzzle Game, players must completed the Al-Quran verses by choosing the right picture. This game is designed for Muslim children aged 3 to 8 years who are in the process of learning the Al-Quran. The testing of this game is done by using black box testing, alpha testing and beta testing with a survey distributed to 23 children under 8 years. The test results show "Hafiz Quran" game has an attractive design, and is easy to use.